Psychological Support and Telehealth Options for Patients with Cancer during the Covid-19 Pandemic in Saudi Arabia - Banaser, Manal; Alshammary, Sami (Integrative Journal of Medical Sciences, 2021)
Background: COVID-19 concerns are associated with an increase in symptoms of depression and anxiety among cancer patients. Telehealth services hold incredible potential for providing psychological support to cancer patients. In a technology-assisted intervention for telehealth, hotline services are a valuable tool to provide psychosocial care. This paper examines the use of hotline services to offer psychological support to cancer patients. Methods: A retrospective analysis of hotline calls patient registry data was conducted. Data were collected from a single cancer center in Riyadh, from May 2020 to March 2021, with a random sample of 877 callers to cancer hotline services. Responses of a satisfaction questionnaire were linked to call-related concerns of registry data. Results: A total of 877 calls were received, the majority of which came from Riyadh locals. Patient disease complaints accounted for 210 calls (24%), while retake medicine requests accounted for 251 calls (28.62%). 143 (16.31%) calls were about scheduled new appointments, 261 calls (29.76%) were about psychological issues induced by Covid-19, such as worry, fear, and anxiety symptoms, and 12 calls (1.37%) having to do with Covid-19. Seven hundred seventy-two callers (88 %) indicated satisfaction with the services call attended. Discussion: Hotline services in cancer care have been identified as a key resource telehealth service that positively influences patient satisfaction and meets cancer patient needs in the face of the pandemic. This study also highlighted the need for other telehealth services, such as mental health mobile applications, virtual multidisciplinary care, and online support groups, which can provide an excellent option for providing psychological support to cancer patients. Conclusion: This study found that providing Cancer Care Hotline services during a pandemic improves patient-centered care and a more efficient healthcare delivery system.